Dyslexia in Elementary School Children: A Systematic Literature Review from a Psycholinguistic Perspective - Singgih, Muhammad; Sa'adah, Nurus; Rachmasisca, Frieska Maryova (Papanda Publisher, 2025)
Dyslexia in elementary school students is often misunderstood as a general learning difficulty, when in fact it stems from disruptions in the brain's language processing system. Therefore, an in-depth exploration of dyslexia from a psycholinguistic perspective is essential. This research aims to identify, examine and provide solutions for learning approaches according to the psycholinguistic needs of dyslexic children. This study was conducted using the Systematic Literature Review (SLR) method with planning, conducting, and reporting stages for eight scientific articles indexed by Sinta in the range of 2020-2025. The findings reveal that: (1) dyslexia at the elementary level is characterized by persistent difficulties in reading, writing, and spelling despite normal intellectual abilities; (2) psycholinguistically, the disorder is rooted in deficits in phonological processing, letter recognition, and verbal working memory; and (3) effective interventions include multisensory strategies, explicit phonics instruction, and the use of visual-auditory learning media that support language acquisition. In conclusion, addressing dyslexia requires an integrative approach that simultaneously targets linguistic, neurological, and emotional dimensions.